Pelatihan pembuatan perangkat pembelajaran berbasis TPACK bagi buru guru Madrasah Al Aziziyah Gunungsari - Hikmah, Nurul; Sarjana, Ketut; Wahyu Triutami, Tabita; Lu’luilmaknun, Ulfa (Rengganis Jurnal Pengabdian Masyarakat, 2023)
TPACK-based learning tool preparation training activity was carried out with the aim of improving teacher professionalism, especially related to making digital media-based learning instruments. This training activity is intended for teachers of Al Aziziyah madrasah teachers, Kapek, Gunungsari, West Lombok. The implementation of activities has been held at Al Aziziyah Islamic Boarding School which is presented in a workshop approach through lectures, discussions, and questions and answers. The presentation includes: Principles of the Independent Curriculum Principles and TPACK, Learning Model Models that Support the Independent Curriculum, Utilization of Learning Media, TPACK with Canva, Simulation , Video and Learning Assessment with Canva. The high motivation and enthusiasm of the participants were seen during the implementation of the service activities, in addition to the positive response of the participants with an enthusiasm level of 90% seen during the implementation of this community service. The very high level of teacher satisfaction with this activity certainly provides very good results in addition to the very high expectations of the teachers for further activities